Allotment Gardens – a valuable ecosystem service - Matos, Rute Sousa (“Synthesizing Different Perspectives on the value of Urban Ecosystem Services”, 2011)
The allotment gardens are a unique contribution to the cityscape. They challenge the conventional notion of urban space and the design of the open spaces, because they are “in growing” and productive urban spaces. They are an echo, a memory of what the countryside has been - a humanized landscape, still accessible in the heart of the city. The benefits of these spaces are multifaceted: socially (leisure, community development, rehabilitation); environmentally (development of ecologically balanced areas, renovation of abandoned urban spaces, diversification of urban land use, increased biodiversity, preservation of the water cycle, the soil cycle and air cycle, reducing the ecological footprint); humanly (improving quality of life, better health, more diversity and food quality); economically (stimulation of local economies); emotionally (the pause that might constitute in the everyday lives of citizens). Considering the interest that allotment gardens have as an urban phenomenon and the existing desire and need of a relationship between the citizens and nature, it’s our believe that these spaces could have a fundamental and decisive role in this relationship. These spaces could have in them all that the city and the man need from nature, including an understanding of the landscape with all its multifunctionality. The aim of this presentation is the inclusion of the allotment gardens in a new design approach to the city's open spaces, aiming at improving the efficiency of multifunctional land uses (production, protection and leisure) and simultaneously ensuring their articulation trough structural and human interfaces able to bring agriculture near to the "urbanscape", to enhance agriculture productivity and added value combined with an increase of biodiversity values and levels of recreational fruition of these different landscapes. In this study will be used as a theoretical support, the authors which consider these spaces as a work material of great potential and value for the creation of new, aesthetically and ecologically viable spaces, as well as some study-cases, namely the allotment gardens in the Metropolitan Area of Lisbon - Portugal, that illustrate the work that has been developed to include these spaces in the city planning. The main outcome of this paper is the creation of a productive and recreational landscape infrastructure that will assure the link and the articulation with the several opens spaces of the city and the connection between them and the countryside.
Keywords: urban agriculture; ecossystem service